KAJIAN FENOMENOLOGI BUDAYA “MENGOPI’ MENGANGKAT PAMOR KOPI LOKAL SEKANAK KOPI PARA RAJA - Amalia, Eva; Arieta, Siti ` (JURNAL MENATA, 2024)
The uniqueness of Indonesian coffee that has spread throughout the world globally and grows into a cultural behaviour and life style . This phenomenology study aim to elaborate specifically on the coffee in Malay culture. Riau Archipelago region did not experience British colonial occupation historically , so it was not familiar with the tea-time culture. Instead, the Malay community knows coffee to be consumed because it has the effect of giving enthusiasm to work due to the caffeine in it. Coffee is also a good complement because it is easy to serve, it just need to brew it with hot water and it pairs well with various snacks. The social behavior of Malay men who like to sit together while waiting to go to sea provides a business opportunity for traders, the Chinese, who have always lived side by side with the Malays of the Riau Archipelago. So from what was originally just a collection of people on the seafront, a coffee tiam coffee shop emerged. “ is one of well known coffee shop with its local brand of coffee called Kopi Sekanak, , Kopi Para Raja “ . This tradition are not only a place to bring together various ages, ethnic backgrounds, religions, and professions but also becoming an icon of Malay’s coffee .